The Defeat of Imperial Urbanism in Québec City, 1840–1855 - McCulloch, Michael (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1993)
In 1840, the City of Québec regained formal corporate status under an ordinance of the Special Council of Lower Canada. This article argues that the ordinance expressed a particular concept or urbanism. Based on concept of the role of cities developed in Great Britain during the Age of Reform, it sought to create non-partisan municipal structures that would encourage local development and 'improvement' while at the same time ensuring the dominance of the anglophone commercial elites. In this, the ordinance expressed in local terms the grand objectives of Governor Charles Poulett Thomson (Lord Sydenham) for the entire colony.Ultimately, this imperial urbanism was a failure. While the essential structure of municipal governance remained intact until 1855, local issues became immediately entangled in provincial party politics. Major business leaders were replaced by professional and small retailers as the dominant group on the City Council. The very ethos of improvement ensured that the under-financed city government became dwarfed by other agencies, such as the banks, the Gas Company and of course railroads. The case of Québec City in the first years of the Union illustrates the failure of attempts to transplant Utilitarian approaches to state formation into a colonial context.